Digital platform to enhance sports tourism in Songkhla province of Thailand - Mattayakorn, Korada; Boonchom, Visit (Edelweiss Applied Science and Technology, 2025)
Digital platforms are innovative tools that effectively enhance sports tourism. The objectives are: 1) to design a digital platform for sports tourism, 2) to develop a web application using Songkhla Province as a case study, and 3) to evaluate the system’s efficiency based on expert and tourist feedback. The development process was guided by the conceptual framework of the Agile SDLC Model, incorporating the Laravel Framework, Bootstrap CSS Framework, Google Maps API, and a CMS-based back-end system. The MySQL database was managed via phpMyAdmin, with chatbot integration through Facebook Messenger. Data from Songkhla's sports tourism agencies formed three categories: Sports Database, Tourism Database, and Facility Database, supported by a back-end system for updating 15 database menus. System efficiency was evaluated by 13 professionals, including digital system experts and tourism professionals, resulting in an average satisfaction score of 4.18 (SD = 0.58), indicating very satisfactory performance. Additionally, 396 sports tourists assessed the system, with an average satisfaction score of 3.92 (SD = 0.40), also indicating high satisfaction. The study demonstrates that developing a digital platform enhances Songkhla Province’s ability to communicate with domestic and international tourists. It supports the promotion of border tourism and adds significant value to the tourism industry. In conclusion, the digital platform provides a modern communication channel for tourists, contributing to Songkhla’s development as a sports city and highlighting the potential of digital solutions to boost the tourism sector.